Analogies: Uses in Teaching - Treagust, David (Springer, 2016)
Over the past two decades, consistent research findings have shown that a variety of external representations used by science teachers, science teacher educators, and science education researchers can lead to successful student learning outcomes. These external representations include analogies, metaphors, and models and model-based learning which have the effect of helping teachers and students externalize their internal mental representations providing avenues for discussion and more focused learning (see for example, Aubusson et al. 2006; Khine and Saleh 2011). This short entry deals with analogies as one form of external representation that is introduced by science teachers and used effectively with both elementary and secondary students when they learn a variety of science concepts.